A7 Drug discovery approach for rare neurological diseases: using novel zinc finger protein technology to develop potential therapy for huntington's disease. (13th September 2016) - Chiocco, Matthew; Choi, Vivian; Graham, Anne-Renee; Klatte, Debra; Francone, Omar; Thomson, David; Zeitler, Bryan; Froelich, Steven; Yu, Qi; Paschon, David E; Miller, Jeffrey C; Marlen, Kimberly; et al.
Abstract : There are approximately 7000 known rare and orphan diseases, over a third of which affect the central nervous system, virtually all do not have adequate treatment options. Shire is committed to developing innovative medicines to treat the fundamental biochemical abnormalities that result in pathologies caused by lysosomal storage disorders and other rare neurological diseases by selecting the right biological target based on extensive knowledge of disease pathophysiology and the right therapeutic modality from our array of technology platforms that includes antibodies, modified RNA, small molecules, gene therapy and protein therapeutics. This approach is particularly relevant for Huntington's disease (HD), a rare and fatal neurodegenerative disease caused by a CAG trinucleotide repeat expansion in exon 1 of one copy of the Huntingtin (Htt) gene, resulting in expression of an aggregation-prone mutant protein. As this mutant protein is believed to be a primary cause of the pathophysiology in HD, Htt-lowering approaches are being explored using various technologies. Here, we will describe the use of an engineered zinc-finger protein transcription factor (ZFP TF) that preferentially down-regulates expression from the disease-causing copy of the Htt gene relative to the normal, unexpanded copy of the gene in both in vitro and in vivo HD models. Results presented here support the further development of allele-specific ZFP TFs as a potential therapy for HD.